Comparison and analysis of 4 drug interaction databases in nephrology patients using clinical pharmacy approaches: A crosssectional study - Eren Demirpolat; Nisa Güneş (İstanbul Journal of Pharmacy)
Background and Aims: Potential drug-drug interactions (pDDIs) might change treatment outcome. pDDIs are frequently encountered in patients with renal dysfunction. Our aim is to analyse the compatibility of drug interaction databases and investigate drug interactions in nephrology patients. Methods: In our study, the treatment orders of patients and a comparison of four databases (Uptodate® , Micromedex® , RxMediaPharma® , Drugs.com) were analysed retrospectively. 152 patients who were treated in a University Nephrology inpatient service between January 2018 and 2020 were included. Results: At least one pDDI was detected in 129 (84.9%) patients. The median age of patients was 62, and the interquartile range was 50-72. A total of 1088 pDDIs belonging to 616 different drug pairs were detected. The age values of patients with at least one pDDI were found to be higher than the group without interaction (p=0.005). The total number of interactions in 4 different databases was significantly higher among patients with polypharmacy and comorbidity (p<0.001). There was an agreement rate of 22% in terms of detecting drug interactions in 4 databases. There was an insignificant level of agreement at the rate of 5.2% in terms of similarity in severity levels. In the pairwise comparison of databases, the highest agreement for identifying interactions (65.3%) and severity levels (21.4%) was between Uptodate® and RxMediaPharma® . Conclusion: The frequency of interaction is high in nephrology. More than one database should be checked due to the low compliance rates between databases by the clinical pharmacist.